2019
DOI: 10.1111/jam.14329
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of probiotic Clostridium butyricum WZ001 on bacterial vaginosis in mice

Abstract: Aims To observe the therapeutic effects of vaginal infusion of probiotic Clostridium butyricum WZ001 on bacterial vaginosis (BV) in mice. Methods and Results Female ICR mice were used to establish the model of BV by infecting oestrogen‐treated mice with Escherichia coli, and then treated with high‐ and low dose of C. butyricum. Clinical indexes of mice in the C. butyricum‐treated groups were significantly improved and comparable to those in the antibiotic group. Pap staining showed that neutrophil count was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Such preventive effects were based on different actions, such as amelioration of inflammatory cytokines, retard sialidase enzyme activity, and reduced G. vaginalis binding capacity to vaginal epithelial cells. In addition, in a recent test on mice, probiotic Clostridium butyricum WZ001 strain not only suppressed the growth of G. vaginalis and decreased inflammatory cytokines but also improved the lactobacilli growth to normalize the vaginal microecological balance ( Zhou et al, 2019 ). A meta-analysis of probiotics-based RCTs for VB treatment reported that currently combo treatments strategies, i.e., probiotics plus antibiotics, are more effective than single applications of both.…”
Section: Health-boosting Spectrum Of Probioticsmentioning
confidence: 99%
“…Such preventive effects were based on different actions, such as amelioration of inflammatory cytokines, retard sialidase enzyme activity, and reduced G. vaginalis binding capacity to vaginal epithelial cells. In addition, in a recent test on mice, probiotic Clostridium butyricum WZ001 strain not only suppressed the growth of G. vaginalis and decreased inflammatory cytokines but also improved the lactobacilli growth to normalize the vaginal microecological balance ( Zhou et al, 2019 ). A meta-analysis of probiotics-based RCTs for VB treatment reported that currently combo treatments strategies, i.e., probiotics plus antibiotics, are more effective than single applications of both.…”
Section: Health-boosting Spectrum Of Probioticsmentioning
confidence: 99%
“…Other reports also displayed that probiotics can inhibit the growth of G. vaginalis in vitro [ 39 ]. Lactic acid may also directly affect host tissues by modulating the immune system and gene expression [ 49 ]. In the present study, the administration of SCBT and VMT reduced the number of G. vaginalis detected in the vagina.…”
Section: Discussionmentioning
confidence: 99%
“…Specific Clostridium has the potential to synthesize antibacterial compounds (Pahalagedara et al, 2020). Zhou et al (2019a) found that Clostridium butyricum WZ001 inhibited inflammation induced by E. coli and maintained vaginal microecological balance in mice. In addition, Romboutsia had the highest proportion in the B. fragilis group.…”
Section: Discussionmentioning
confidence: 99%